The interrelatedness of error prevention and error management - Van der Byl, Connie A.; Vredenburg, Harrie (Frontiers in Psychology, 2023)
We study errors in organizations to understand and ideally prevent them from reoccurring. In this study we examine mistakes made as an oil company adopted new technology to access untapped reserves. We find that a pre-existing error management culture (EMC) dominated in the organization while error prevention measures were deficient. This is surprising given the complexity of the business and the importance of safety. We show that a balance between error prevention and error management is difficult to achieve owing to the contradictory nature of these approaches. While the extant organizational error literature identifies the complementary aspect of error prevention and error management it does not consider their interrelatedness–how one affects the other. We find that the dominating error management culture at Suncor Energy contributed to error prevention processes that were misapplied, informal or absent. This highlights the need for deliberate examination of error approaches especially as the business context shifts.